THE PRESENT AND FUTURE CHALLENGES AND THREATS OF DEVIANT SECTS AND SCHOOLS IN THE MAHDAVI CULTURE - Dorcheh, Javad (Revista Inclusiones, 2019)
Mahdaviat is one of the most important Islamic and Shia doctrines that has the capacity to create unity and coherence and security in the internal and international dimensions. Deviant currents and sects through different ways have attempted to divert these doctrines; sometimes through forging and deviation of defensive and security doctrines and sometimes through creating violence and confusion and dispute in the name of Shite and Mahdaviat. These activities can in addition to distorting the transcendent culture, result in several insecurity problems and the prospect of these sects also indicate dispute, contention and destruction; therefore, the main issue is that what are the present and future challenges and threats of the deviant sects and schools? To confront the challenges can using the rich Mahdavi culture, suitable teaching and research regarding the sects and also an accurate and systematic planning and implementing them provide immunity against these threats.